Insurgent practices of ‘communal place making': repair and prefiguration at the Cissie Gool House occupation in Cape Town - Cosentino, Tommaso (Department of Environmental and Geographical Science, 2026)
Occupations of land and abandoned buildings are one of the main ways in which marginalized urbanites in South Africa claim their share of the urban space and make a home for themselves. However, these housing solutions and their inhabitants are often criminalized through political discourse, legal actions and police-enforced evictions. The work of autoconstruction and repair carried out by residents of housing occupations tends to be overlooked by planners and local politicians. In order to shift the perception and understanding of such practices, this study aims to explore the insurgent practices of ‘communal place-making' performed by the residents of Cissie Gool House – a large housing occupation in Woodstock, Cape Town. Through a Participatory Action Research framework, I focus on residents' stories of involvement in the occupation's organizational structures and communal projects, including the Security and Safety Task Team (SSTT), the community kitchens and vegetable garden, and the weekly Monitors Meeting. Through a workshop on storytelling and complementary methods such as focus groups and in-depth interviews, I gained insights on the junctures between individual and collective forms of spatial agency. These are discussed in relation to debates on popular and peripheral urbanization. By looking at the shared ways to address intergenerational trauma, this study advances the concept of ‘repair as healing' to describe the more-than-material practices of repair that sustain the community of residents. This dissertation also explores the prefiguration of alternative urban futures embedded in insurgent planning actions by looking at existing communal projects in the occupation. Finally, by looking at the work of the SSTT addresses the risk of celebrating forms of reactionary insurgency if they are studied without proper historical and political contextualization.